Nanocompósitos com atividade antioxidante de amido de milho/isolado proteico de soro de leite/ óleo essencial de alecrim obtidos por extrusão termoplástica - Azevedo, Viviane Machado de (2016)
In order to improve the quality and safety of food, the active packaging emerges as a new technology based on the release of composites beneficial to food products. Thus, biodegradable films incorporated with active substances have the function of acting as a barrier to external elements, protecting the product and increasing its shelf life. They are formulated from proteins, polysaccharides, lipids or from the combination of these compounds. However, there is a need to improve the performance properties of these packages. Nanotechnologies, then, emerges with the study of many nanoparticles as additives to modify the performance of biodegradable polymers. With this, we aimed at developing and active antioxidant film of corn starch blenders and whey protein isolate with rosemary essential oil or microcapsules of rosemary essential oil reinforced with sodium montmorillonite (MMTNa + ) nanoparticles by extrusion. The films were developed and characterized in a first stage for the selection of the best polymeric blender using the following analyses: water vapor permeability (WVP), machanical properties; optical, thermogravimetry (TG), differential scanning calorimetry (DSC), x-ray diffraction (XRD) and scanning electron microscopy (SEM). In the second stage, montmorillonite clay nanoparticles and rosemary essential oil were added as reinforcement to evaluate its antioxidant effect. In a third stage, we studied the addition of microcapsules of rosemary essential oil (MR) as a form of protecting the active agent and its antioxidant potential in the films. The results indicate that the development of p olymeric blender with 30% of corn starch substitution is the most indicated for future work. The addition of rosemary essential oil or microcapsule of rosemary essential oil allowed for the obtaining of nanocomposites with antioxidant potential for application in food packages.